Weightbearing after combined medial and lateral plate fixation of AO/OTA 41-C2 bicondylar tibial plateau fractures: a biomechanical study - Sorawut Thamyongkit (2022)
Background: Combined medial and lateral plate fixation is recommended for complex tibial plateau fractures with medial fragments or no cortical bone contact. Although such fixation is adequate to resist forces during range of motion, it may be insufficient to support immediate postoperative weightbearing. Here, we analyzed displacement, stiffness, and fixation failure during simulated full weightbearing of bicondylar tibial plateau fractures treated with combined medial and lateral locking plate fixation. Methods: We used 10 fresh-frozen adult human cadaveric tibias and mated femurs. Osteotomies were performed with an oscillating saw and cutting template to simulate an AO Foundation and Orthopaedic Trauma Association (AO/OTA) 41-C2 fracture (simple articular, multifragmentary metaphyseal fracture). Specimens were anatomically reduced and stabilized with combined medial and lateral locking plates (AxSOS, Stryker, Mahwah, NJ). Specimens were loaded axially to simulate 4 weeks of walking in a person weighing 70 kg. The specimens were cyclically loaded from 200 N to a maximum of 2800 N. Then, if no failure, loading continued for 200,000 cycles. We measured displacement of each bone fragment and defined fixation failure as ≥5 mm of displacement. Construct stiffness and load at failure were calculated. Categorical and continuous data were analyzed using Chi-squared and unpaired t-tests, respectively. Results: Mean total displacement values after 10,000 loading cycles were as follows: lateral, 0.4 ± 0.8 mm; proximal medial, 0.3 ± 0.7 mm; distal medial, 0.3 ± 0.6 mm; and central 0.4 ± 0.5 mm. Mean stiffness of the construct was 562 ± 164 N/mm. Fixation failure occurred in 6 of 10 specimens that reached 5 mm of plastic deformation before test completion. In the failure group, the mean load at failure was 2467 ± 532 N, and the mean number of cycles before failure was 53,155. After test completion, the greatest displacement was found at the distal medial fracture site (2.3 ± 1.4 mm) and lateral fracture site (2.2 ± 1.7 mm). Conclusions: Although combined medial and lateral plate fixation of complex tibial plateau fractures provides adequate stability to allow early range of motion, immediate full weightbearing is not recommended.